Calculation of Carbon Emissions and Sequestration to Support the Net Zero Emission Target of Central Java Province (Case Study: Cilacap and Brebes Regencies) - Amru, Khaerul; Anjani, Raissa; Aryantie, Melania Hanny; Ihsan, Iif Miftahul; Oktivia, Ressy (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Indonesia's net zero emission target is being achieved through greenhouse gas (GHG) inventories using the Intergovernmental Panel on Climate Change (IPCC) method. This study aims to determine the potential contribution of the Brebes and Cilacap Regencies using the net zero target of Central Java Province in terms of carbon sequestration in various types of land cover. Land-cover data were collected from the RBI. Land cover use data were then multiplied by the constant value of carbon stocks to determine the potencies of carbon sequestration and storage. The potential contribution of carbon sequestration in Brebes Regency reaches 3,882,850.81 tons of CO2 eq or 4.60%, while Cilacap Regency has almost two times the potential for carbon sequestration in Brebes, which is 7,191,181.44 tons of CO2 eq, or equivalent to 8.52% of the total carbon emissions of Central Java Province which reached 84,435,352.5 tons of CO2 eq. This difference in carbon sequestration potential was most influenced by the presence of mangrove and terrestrial forests, with the highest value of carbon stock constants compared to other land uses. Overall, these two regencies canabsorb almost 1/3 of the carbon emissions in Central Java Province; therefore, they can be prioritized in efforts to increase carbon sequestration at the provincial level.